The role of local economic development (LED) in the post-war reconstruction of communities - Su, Yanyin (Kharkiv : V. N. Karazin Kharkiv national university, 2025)
The master's thesis is devoted to the study of local economic development (LED) as an important tool for the post-war reconstruction of territorial communities in Ukraine. The research examines theoretical approaches, principles, and models of LED, as well as analyzes the economic impact of armed conflicts on community development. Special attention is paid to the analysis of international experience in post-war recovery, particularly the practices of China and other countries. The study explores financial and institutional mechanisms that support community development and evaluates their potential application in Ukraine. Based on the research results, practical recommendations and mechanisms for improving LED policy in Ukraine are proposed, including the adaptation of Chinese experience to strengthen the economic resilience and sustainable development of Ukrainian territorial communities.
Роль місцевого економічного розвитку (МЕР) у післявоєнній відбудові громад
Scientific supervisor: Швайко Мар’яна Леонідівна, кандидат економічних наук, доцент кафедри фінансів, банківської справи та страхування
Keywords: SOCIAL SCIENCES::Business and economics::Business studies; local economic development; місцевий економічний розвиток; territorial communities; територіальні громади; multi-level governance; багаторівневе управління; fiscal decentralization; фіскальна децентралізація